2012
DOI: 10.1002/etc.1725
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, fate, and persistence of gemfibrozil in water and soil

Abstract: Pharmaceuticals and personal care products (PPCPs) have emerged as a group of potential environmental contaminants of concern. The occurrence of gemfibrozil, a lipid-regulating drug, was studied in the influent and effluent at a wastewater treatment plant (WWTP) and groundwater below a land application site receiving treated effluent from the WWTP. In addition, the sorption of gemfibrozil in two loam soils and sand was assessed, and biological degradation rates in two soil types under aerobic conditions were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 44 publications
1
41
1
1
Order By: Relevance
“…Since primidone was found to be persistent in all previous studies Hass et al, 2012;Burke et al, 2014a;Henzler et al, 2014), we refrain from linking its degradation behavior to the potentially prevailing redox conditions below the pond. For most of the degrading compounds the estimated rate constants of this study were considerably higher than reported in previous studies, even though prolonged aerobic conditions, which generally lead to higher degradation rates for many organic compounds (Stuyfzand et al, 2007;Kunkel and Radke, 2008;Xu et al, 2009;Wiese et al, 2011;Fang et al, 2012;Hoppe-Jones et al, 2012), were presumably not present. Flow path averaged degradation constants lay between 0.036 d −1 for clofibric acid and 0.9 d −1 for ibuprofen.…”
Section: Substancecontrasting
confidence: 76%
“…Since primidone was found to be persistent in all previous studies Hass et al, 2012;Burke et al, 2014a;Henzler et al, 2014), we refrain from linking its degradation behavior to the potentially prevailing redox conditions below the pond. For most of the degrading compounds the estimated rate constants of this study were considerably higher than reported in previous studies, even though prolonged aerobic conditions, which generally lead to higher degradation rates for many organic compounds (Stuyfzand et al, 2007;Kunkel and Radke, 2008;Xu et al, 2009;Wiese et al, 2011;Fang et al, 2012;Hoppe-Jones et al, 2012), were presumably not present. Flow path averaged degradation constants lay between 0.036 d −1 for clofibric acid and 0.9 d −1 for ibuprofen.…”
Section: Substancecontrasting
confidence: 76%
“…However, no PPCP compound was detected in the gravity drainage collected at the depth of 100 cm below ground surface. Fang et al (2012) reported that the gemfibrozil in reclaimed water applied on land might reach the groundwater aquifer underneath. These field-observed results provided a snapshot of the PPCP chemicals in motions, but were unable to delineate the dynamic interactions between the chemicals, hydraulics, and nature of soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…For gemfibrozil the range of the log K FOC values (representing OC-normalized distribution coefficients at the solution concentration of 1 mg L À1 ) includes that reported in the literature for the log OC-normalized distribution coefficients (K OC , Lkg À1 ) varying between 1.9 and 2.9 on different soils at relevant pH (Lin et al, 2011;Fang et al, 2012). The range of the triclosan log K FOC values presented in Table 3 is within the wider log K OC range of 3.0-4.3 reported on various soils at comparable pHs (Karnjanapiboonwong et al, 2010;Duran-Alvarez et al, 2012).…”
Section: The Oc-normalized Freundlich Constantsmentioning
confidence: 99%